Exploring the Role of Internal Control Effectiveness, Information Asymmetry, and Individual Morality in Accounting Fraud: Insights from the Public Sector - Riky Sai Maruli (Universitas Hayam Wuruk Perbanas, 2026)
Accounting fraud remains a serious issue that can disrupt organizational governance and reduce financial transparency, particularly in the public sector. Based on the Fraud Triangle Theory, fraud is driven by pressure, opportunity, and rationalization, which are reflected in organizational conditions and individual behavior. This study examines the effects of internal control effectiveness, information asymmetry, and individual morality on the likelihood of accounting fraud. This research employs a quantitative approach with a causal-comparative design, using primary data collected through questionnaires distributed to 96 respondents working in finance, accounting, and budget management fields. The sample was selected using purposive sampling, and the data were analyzed using IBM SPSS Statistics. The results indicate that internal control effectiveness and information asymmetry significantly affect the probability of accounting fraud, while individual morality does not. Simultaneously, the three variables do not significantly affect the probability of fraud. These findings suggest that organizational factors, particularly the quality of internal control systems and the level of information transparency, play a more dominant role than individual moral factors in preventing fraud. The practical implication of this study is that decision-makers in the public sector should strengthen internal control systems and enhance information transparency as key strategies to minimize the risk of accounting fraud.